SUMBANGAN BERMAKNA PONDOK GONTOR DAN MASA DEPAN INDONESIA - H. Haikal (Millah: Journal of Religious Studies, 2013)
Based on this unfavourable condition the Trimurti of K.H. Ahmad Sahal, K.H. Zainuddin Fananie, and K. H. Imam Zarkasyi strived their best to change this situation bj founding Pondok Modern Gontor (PMG) and stress-ing the important of Arabic and English languages. Almost without anything or with very limited preparation th y began founding tarbiyatul atfal, preschool. Almost all o f its students were local children. However, theirjihad, working and studying hard after the founders and material and moral supports of its sympathiser done step by step, PMG has been growing slower, and later faster, especially after returning of K.H. Imam Zarkasyi finished his study in many different places such as Sala and Sumatera Barat, or Sumbar. A s the condition of PMG getting better and better, many students from many different places are coming to study at PGM which already focused on teaching students at the level junior and senior high schools, and then finally university.